Kepemimpinan Transformasional Pada Lembaga Pendidikan Islam di Indonesia - Ekawati, Melinda Nur; Hamami, Tasman (Paedagogie, 2026)
This study aims to analyze the implementation of transformational leadership in Islamic educational institutions in Indonesia, focusing on pesantren and madrasah. Transformational leadership is considered an approach that can drive positive change in an institution or organization, achieved through idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This research analyzes how the transformational leadership style is implemented in two Islamic educational institutions that have opposing educational systems: the non-formal education system of pesantren, which is based on religious traditions, and the formal education system of madrasah, which is more structured in curriculum and administration. This study uses a qualitative approach with a literature review method. The findings show that the principles of transformational leadership can be applied in both Islamic educational institutions, albeit through different approaches. In pesantren, the central figure is the Kiai, who holds a central role with his spiritual and charismatic power, while in madrasah, transformational leadership emphasizes professional management and systematic institutional administration. This study contributes to the development of leadership theory in Islamic educational institutions and provides practical strategies for improving the quality of educational institutions and the development of student character.